EFFECT OF LIME AND PHOSPHORUS APPLICATION ON THE SULPHATE ADSORPTION CAPACITY OF SOUTH WESTERN NIGERIAN SOILS - ADETUNJI, M. T. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2020)
The influence of phosphate and lime additions on the adsorption characteristics of some representative soils of Southwest Nigeria was investigated in the laboratory. Preliminary studies revealed that the Lime Requirements (LR) of the soils varied from 1.6g/kg to 3.6g/kg, while the Standard Phosphorus Requirements (SPR) ranged from 80ppm to 185ppm. Lime and phosphate were added to the soil according to the LR and the SPR values. Reduction in sulphate adsorption varied from 20 to 31% as a result of P addition alone and a more pronounced depression in sulphate adsorption was observed when lime alone was added. Adding both to soils the same time resulted in reduction from 48 to 68% in sulphate adsorption capacity of soils. It was observed that the addition of lime and P did not only lower the adsorption of sulphate in soils but also caused the displacement of up to 7m of the adsorbed sulphate, suggesting high leaching losses of sulphur in soils receiving high phosphorous fertilizer application and the induced deficiency of sulphur in such soils.